Bunga Edelweiss sebagai Ide Penciptaan Motif Batik Kontemporer pada Busana Wanita - Kencana, Dwi; Pebriyeni, Eliya (YASIN, 2025)
Batik as Indonesia's cultural heritage continues to develop following the dynamics of the times, but exploration of rare flora motifs that are full of meaning is still relatively limited. This research aims to create a contemporary batik motif inspired by the Edelweiss flower, a typical mountain plant that symbolizes eternity and constancy. This research uses the art creation practice method with five stages: preparation, elaboration, synthesis, concept realization, and completion. The subject of the research is the researcher himself with support from the supervisor and direct observation of visual objects. Data were collected through observation, visual documentation, literature study, and process reflection, then analyzed descriptively-qualitatively. The research resulted in seven works of contemporary batik tulis in the form of women's clothing depicting the growth cycle of Edelweiss, from pollination to flower drying. The visualization is realized through a combination of colet and dyeing techniques, as well as harmonious and expressive motif arrangement. Each work elevates the symbolic value of Edelweiss flowers into a communicative and meaningful visual form. In conclusion, the creation of Edelweiss batik motifs in this fashion work proves that rare flora motifs can be appointed as the main inspiration in contemporary batik, as well as a medium of expression of philosophical and reflective values that are relevant to the spirit of nature and culture conservation in the modern era.